E-commerce website as a sales channel for Small Medium Enterprises (SME) / Anis Suraya Daud - Daud, Anis Suraya (Faculty of Business and Management, 2010)
Pernec Corporation Berhad has introduced the Halal square portal e-commerce website as a sales channel for Small Medium Enterprises (SME) and the problem statement has been identified that low number of visitors in portal, many competitors out there provides same services with Halal Square and low sales on online transaction.